The Role of Biotechnology in Plant Breeding for Sustainable Agriculture in Brazil - Derk, Knapen; Nathan, Scherer; Jonathan, Orozco (Techno Agriculturae Studium of Research, 2024)
Sustainable agriculture is a critical goal for Brazil, a country with vast agricultural potential and significant biodiversity. Biotechnology has emerged as a powerful tool in plant breeding, offering innovative solutions to enhance crop productivity, resilience, and sustainability. Integrating biotechnological methods into traditional breeding programs holds promise for addressing the challenges of climate change, pests, and diseases. This study aims to investigate the role of biotechnology in plant breeding to promote sustainable agriculture in Brazil. The research seeks to evaluate the effectiveness of biotechnological interventions in improving crop yields, resistance to biotic and abiotic stresses, and overall agricultural sustainability. A mixed-methods approach was employed, combining quantitative analysis of crop performance data with qualitative insights from interviews with agricultural experts and biotechnologists. Field trials were conducted across various regions in Brazil to assess the impact of genetically modified crops and other biotechnological innovations on agricultural outputs. Data on crop yields, pest resistance, drought tolerance, and environmental impact were collected. The findings indicate that biotechnological approaches significantly enhance crop performance, including genetic modification and marker-assisted selection. Crops developed through biotechnology showed increased yields, improved resistance to pests and diseases, and better adaptation to environmental stresses. Additionally, these crops required fewer chemical inputs, reducing environmental pollution and promoting sustainability. Biotechnology is pivotal in advancing plant breeding for sustainable agriculture in Brazil. Integrating biotechnological methods into traditional breeding programs has proven effective in addressing critical agricultural challenges, leading to enhanced crop productivity and environmental sustainability. These findings underscore the importance of continued investment in biotechnological research and development to support sustainable farming practices in Brazil.